2017
DOI: 10.1136/bmj.j3078
|View full text |Cite
|
Sign up to set email alerts
|

Risk of post-pregnancy hypertension in women with a history of hypertensive disorders of pregnancy: nationwide cohort study

Abstract: Objectives To determine how soon after delivery the risk of post-pregnancy hypertension increases in women with hypertensive disorders of pregnancy and how the risk evolves over time. Design Nationwide register based cohort study. Setting Denmark. Populations 482 972 primiparous women with a first live birth or stillbirth between 1995 and 2012 (cumulative incidence analyses), and 1 025 118 women with at least one live birth or stillbirth between 1978 and 2012 (Cox regression analyses). Main outcome measures 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(220 citation statements)
references
References 31 publications
8
205
2
5
Order By: Relevance
“…The risk of hypertension after the combined exposure of preeclampsia and GH was greatest after 4 years (HR: 9.4; 95% CI, 8.0–11.0) and declined with increasing follow‐up time. A similar result was reported by Behrens et al, who found that in the year after delivery, women with HDP had 12‐ to 25‐fold higher rates of hypertension than did women with normotensive pregnancies 59. The rates remained 3‐ to 10‐fold higher from 1 to 10 years postpartum and decreased to roughly twice as high at ≥20 years postpartum.…”
Section: Hdp and Early To Midterm Risk Of Maternal Cvdsupporting
confidence: 86%
“…The risk of hypertension after the combined exposure of preeclampsia and GH was greatest after 4 years (HR: 9.4; 95% CI, 8.0–11.0) and declined with increasing follow‐up time. A similar result was reported by Behrens et al, who found that in the year after delivery, women with HDP had 12‐ to 25‐fold higher rates of hypertension than did women with normotensive pregnancies 59. The rates remained 3‐ to 10‐fold higher from 1 to 10 years postpartum and decreased to roughly twice as high at ≥20 years postpartum.…”
Section: Hdp and Early To Midterm Risk Of Maternal Cvdsupporting
confidence: 86%
“…A possible relationship between GH and risk of maternal CVD has been studied to a much smaller extent. While several studies have reported a significant association between GH and subsequent CVD,5, 19, 20, 23, 24, 25, 26, 27, 28, 29, 30 only 4 of these had a comparable cohort size and a similar follow‐up time compared with our study 19, 20, 23, 29. None of these studies looked at the combined effects of GH, SGA infant, preterm delivery, and parity as predictors of subsequent CVD.…”
Section: Introductionmentioning
confidence: 66%
“…studied approximately 6000 normotensive women who developed HDP and reported more than twice the risk for pre‐hypertension or hypertension in the year after delivery compared with those without HDP. A report by Behrens et al . found a 12–25‐fold higher rate of hypertension 1 year after birth among women with HDP compared with normotensive parturients.…”
Section: Placental Syndromesmentioning
confidence: 97%